Hepatitis B Virus Large Envelope Protein Interacts with γ2-Adaptin, a Clathrin Adaptor-Related Protein - Hartmann-Stühler, Cora (American Society for Microbiology, 2001)
For the outcome of a hepatitis B virus (HBV) infection, the viral L envelope protein with its pre-S domain performs pivotal functions by mediating attachment of HBV to liver cells, envelopment of viral capsids, release of (sub)viral particles, regulation of supercoiled DNA amplification, and transcriptional transactivation. To assess its multiple functions and host-protein assistance involved, we initiated a two-hybrid screen using the L-specific pre-S1 domain as bait. With this approach, we have identified γ2-adaptin, a putative member of the clathrin adaptor proteins responsible for protein sorting and trafficking, as a specific binding partner of L protein. Evidence for a physical interaction between L protein and γ2-adaptin was also demonstrated by affinity chromatography and coimmunoprecipitation, and the binding sites were mapped to the L-specific pre-S1 domain and the γ2-adaptin-specific ear domain. The specificity of the interaction was further sustained by the failure of γ1-adaptin, a closely related γ2-adaptin homologue, to associate with L protein. Analysis of an L mutant protein indicates that the L–γ2-adaptin interaction strictly depends on the pre-S1 domain of transmembrane L protein oriented to the cytosol and thus appears to occur in the cytosolic environment. Interestingly, coexpression of the two interacting partners in transfected cells resulted in recruitment of γ2-adaptin by L protein onto cis-Golgi-like structures, strongly indicating that the association is physiologically relevant. Together, the results suggest a role for γ2-adaptin in L-mediated processes of viral biogenesis and/or pathogenesis, such as facilitating and guiding HBV assembly.